Preparation of Aluminum doped Zinc Oxide Thin Films on Glass Substrate by Sparking Process and Their Optical and Electrical Properties - A. Sukee (2018)
© Published under licence by IOP Publishing Ltd. Aluminum doped Zinc Oxide (AZO) nanoparticle thin films were deposited on glass substrates by a double tip sparking process. The effect of Al doped ZnO on electrical and optical transmittance properties were studied. The doping ratios of Al into ZnO were 3, 5, 7, 13 and 22 %. SEM images indicated particle size decreased with increasing the Al content after annealing. Raman spectra results of AZO films associated with the hexagonal structure. AZO films have an average transmittance in visible region at 60 %. The energy gap increased with increasing Al content. The minimum resistivity was found at 5 % of Al doping for AZO film.